Decent work in Malawi: social security; extension of social insurance to all workers - Khembo, Loness (Institute of Development and Labour Law, 2015)
The only way Malawi can ensure adequate social security coverage to her citizens is to extend the scope and coverage of social security benefits provided by the labour legislations to all workers as they are more reliable and less burdensome on the poor state. This is premised on the fact that most Malawians work, but only a few are employees as shall be seen later in this chapter. This will reduce the burden on the state of providing social security to all her citizens as most will be covered by social insurance. It is against this background that this study analyses the Malawian pieces of legislation on social security with the aim of identifying the gaps that are affecting social security coverage to Malawian workers. In doing so, these legislations will be examined against the relevant international conventions specifically the ILO C 102 and the SADC Code. The study will also focus on how best to improve social security benefits coverage in Malawi and making it more relevant to Malawians.